COMPREHENSIVE DEVELOPMENT OF RURAL AREAS: THE LEGAL SPECIFICS OF STATE PROGRAMS - Dolzhenkov, Valeriy; Sidorova, Natalia; Khodzhaliev, Salekh (Revista Inclusiones, 2020)
The article considers the legal aspects of forming and implementing state programs as a legal mechanism for ensuring the comprehensive development of rural areas. Having powerful economic, demographic, natural and cultural potential, rural areas lag behind urban areas. The study aims at analyzing the possibility of using state programs for the purposes of the comprehensive development of agricultural territories. The authors of the article dwell on the historical formation of state programs for the development of rural areas in the Russian Federation. In practice, the implementation of such programs is hindered by such factors as underdeveloped infrastructure, hidden unemployment and low living standards of the rural population. The authors study the international experience of states in the development and support of rural areas and highlight its specifics in different countries. They suggest adopting some positive examples when developing new programs and improving the existing ones in the Russian Federation.